2021
DOI: 10.1007/s12020-020-02568-y
|View full text |Cite
|
Sign up to set email alerts
|

Neck complaints before and after uncomplicated thyroidectomy: prevalence, postoperative outcome and relationships with thyroid weight and reflux like symptoms

Abstract: Purpose The surgical thyroid disease includes upper aerodigestive complaints with not homogenous prevalence and specific features. The purpose was to analyze before and after total thyroidectomy (TT) the prevalence and severity of voice, swallowing, respiratory, and reflux airway symptoms in relation with thyroid weight. Methods A total of 98 consenting patients undergoing TT were enrolled. Preoperatively, 1 and 3 months after TT, patients underwent videol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…15,17,21 The rest of the authors included both benign and malignant lesions. 14,[18][19][20]22,23 3.1 | Swallowing and voice outcomes…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…15,17,21 The rest of the authors included both benign and malignant lesions. 14,[18][19][20]22,23 3.1 | Swallowing and voice outcomes…”
Section: Resultsmentioning
confidence: 99%
“…The swallowing impairment score and the eating assessment tool‐10 were both subjective outcomes used in studies 15,17,20 . In the controlled study of Sober et al, 22 patients who underwent total or partial thyroidectomy reported higher swallowing impairment score than healthy individuals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations